2012
DOI: 10.1007/s10140-012-1101-9
|View full text |Cite
|
Sign up to set email alerts
|

Finding nemo: imaging findings, pitfalls, and complications of ingested fish bones in the alimentary canal

Abstract: In Asian cuisine, fish is often prepared whole with the bones. Accidental fish bone (FB) ingestion is not an infrequently encountered condition in the emergency department. An impacted FB in the alimentary canal can lead to potentially life-threatening complications. For impacted FBs that cannot be visualized clinically, radiographs and multidetector computed tomography are helpful in localizing the FB, evaluating for complications, and planning treatment. In this pictorial essay, we illustrate the spectrum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…For patients in the 'fish bone negative' group, if there was a clear history of recent fish bone ingestion, it was assumed that the ingested fish bone had been swallowed and passed further down the alimentary tract; it has been shown that abrasion from an ingested foreign body produces the same symptoms as the presence of the foreign body itself. (1) When the risk factors between the 'fish bone positive' and 'fish bone negative' groups were compared using Fisher's exact test or chi-square test, the only risk factor that showed a statistically significant difference was the use of dentures. The 'fish bone positive' group had a higher proportion of patients using dentures (25/87 vs. 4/25, p = 0.04).…”
Section: Resultsmentioning
confidence: 99%
“…For patients in the 'fish bone negative' group, if there was a clear history of recent fish bone ingestion, it was assumed that the ingested fish bone had been swallowed and passed further down the alimentary tract; it has been shown that abrasion from an ingested foreign body produces the same symptoms as the presence of the foreign body itself. (1) When the risk factors between the 'fish bone positive' and 'fish bone negative' groups were compared using Fisher's exact test or chi-square test, the only risk factor that showed a statistically significant difference was the use of dentures. The 'fish bone positive' group had a higher proportion of patients using dentures (25/87 vs. 4/25, p = 0.04).…”
Section: Resultsmentioning
confidence: 99%
“…3C ) [ 46 ]. CT has high sensitivity (90% to 100%) and specificity (93.7% to 100%) [ 47 - 50 ]. CT sensitivity may increase with three-dimensional reconstruction, i.e., coronal or sagittal views [ 51 ].…”
Section: Fish Bone Foreign Body In the Esophagus And Pharynxmentioning
confidence: 99%
“…Some authors report up to 100% sensitivity on retrospective review of their images [ 7 ]. Fishbones appear as high-density linear objects surrounded by inflammatory changes of the adjacent bowel and can be visualized on thin slice images of no more than 2 mm [ 8 , 9 ]. Multiplanar reconstructions can increase sensitivity further [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%